Smart Grids : Infrastructure, Technology, and Solutions - Borlase, Stuart (Boca Raton : CRC Press, 2013)
This book discusses the smart grid, currently the hottest topic in the electric utility market. It details in-development and existing technologies composing the smart grid solution framework used in electrical infrastructure. International contributors share their perspective to explore the role of the utility industry and standards in smart grid development. They detail the initiatives and organizations driving efforts. Detailing recent successful real-world implementations, this reference examines critical factors for successful smart grid deployment, from utility, regulatory, and consumer perspectives. It then explores the technologies and business drivers that will propel next-generation smart grid technology--
ch. 1. Overview of the electric utility industry -- ch. 2. What is smart grid, why now? -- ch. 3. Smart grid technologies -- ch. 4. Smart grid barriers and critical success factors -- ch. 5. Global smart grid initiatives -- ch. 6. Smart grid : where do we go from here?
Keywords: Smart power grids; Electronic books